Diseño y simulación de una férula antiequino (afo) en pla y abs mediante software cad/cae aplicado en la deformidad en equino de pie y tobillo - Viteri Jaramillo, Analhi Diamela (2025)
This study addresses the design and simulation of an ankle-foot orthosis (AFO), also known as an anti-equinus splint, using CAD/CAE software, with the aim of improving the treatment of foot and ankle equinus deformity. Equinus deformities, characterized by excessive plantar flexion, are common in patients with muscle, nerve, or tendon injuries and can cause difficulties in walking. The use of conventional anti-equinus splints has limitations due to their standardized design, which can lead to discomfort and ineffective immobilization. The objective of the study was to design an anti-equinus splint using virtual models of feet and ankles based on anthropometric data from the Latin American population, to ensure precise fit and improve functionality. The methodology employed was quantitative, based on the use of CAD software to create a detailed model of the splint and CAE software to simulate its behavior under different loading conditions. The polymeric materials used were PLA (Polylactic Acid) and ABS (Acrylonitrile Butadiene Styrene), subjected to different loads to evaluate their mechanical stress, deformation, and displacement. The results indicated that both materials have similar capabilities to withstand stress, but PLA exhibited less deformation and displacement compared to ABS, suggesting it is more suitable for applications requiring greater dimensional stability. Under the maximum load of 200 kg, the displacement of PLA was 3,509 μm, while that of ABS was 6,182 μm. Regarding deformation, PLA showed a rate of 5,996 × 10⁻⁵ %, significantly lower than that of ABS 1,051 × 10⁻⁴ %. In conclusion, the use of CAD/CAE software allows for the creation of customized splints that better fit the patient's anatomy, improving the comfort and effectiveness of treatment. This approach represents an advance in the design of orthopedic devices and a well-founded basis for the development of future research to optimize their use.